Effect of heating and enzymatic hydrolysis on casein cow milk sensitivity in Moroccan population - Ouarda Azdad (Taylor & Francis Group, 2018)
The objectives of the present work were first to evaluate the sensitivity to cow raw milk of the population of Fez, and then to study the effect of heating and pepsin hydrolysis on the allergenicity of casein. A cross-sectional study was carried out in Fez Hospitals, in which 1000 patients were recruited to establish a sera bank used to evaluate specific IgE to cow milk and to casein. Then, we evaluated the reaction of human IgE to heated and pepsin-hydrolysed casein. The results showed that 11.5% of the population studied self-reported reactions to foods. From them, 3.6% reported allergy to milk. Evaluation of specific IgE to cow raw milk showed that 11.9% of patients presented higher specific IgE levels. The treatments of casein indicated that both heating and pepsin hydrolysis totally decreased its binding on the human IgE.